Analysis of the Effect of U-Turn Access Closure on the Performance of Gajah Mada Road, Batam Indonesia - Saputra, Tohmas; Rifai, Andri Irfan; Isradi, Muhammad; Prasetijo, Joewono (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Gajah Mada Road, Batam Taman Kota area is a primary collector road 1 that has a U-Turn and dense current if passed by motorists on weekdays in the afternoon. This study aims to analyze road performance due to the closure and opening of U-Turn access. Design/methodology/approach: The research method used systematic observation is carried out on Mondays and Fridays (weekdays when the U-Turn is closed and opens) at 17.15 - 18.00 WIB in MKJI 1997. Findings: The volume of vehicles and the average speed of vehicles passing when the U-Turn is closed is higher compared to the U-Turn is opened. Meanwhile, the level of road service (LoS) is classified as good because of the stable current and normal volume even though the vehicle speed is limited and affected by traffic. Research limitations/implications: The U-Turn closure policy is believed to be a solution to reducing vehicle congestion. Practical implications: Vehicle buildup factors due to U-Turn access are the main factors hampering road performance. Originality/value: This paper is an original work. Paper type: Research papers.